Foreword to the special issue on "Building a sustainable future: New Asian regionalism in international economic law" - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2022)
We live in an unprecedented time, which witnesses the rapid transformation of global trade and politics. The neoliberal legal order in the post-war era has recently encountered multifaceted threats. Rising populist nationalism, US-China tensions and the COVID-19 pandemic have led to diverse forms of trade protectionism that has eroded the normative basis of international economic law. The Russian invasion of Ukraine and corresponding economic sanctions have further worsened the instability of the increasingly fragile supply chain and multilateral trading system. Amid these challenges, new Asian regionalism has emerged to shape and construct the new regional economic order. In response to declining hegemonic powers, developing countries in Asia have utilized their collective power to influence global rulemaking. New EU and US Indo-Pacific strategies also recognize the shift of the economic center of gravity to Asia and seek to enhance their involvement in the region. These developments not merely cement the foundation for the multipolar world, but also serve as a catalyst for trade liberalization. The core pillars of new Asian regionalism include the Association of Southeast Asian Nations (hereinafter "ASEAN") and the mega-regional trade agreements including the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (hereinafter "CPTPP") and the Regional